BUILD CAPACITY FISHERMAN: IMPORTANCE OFF INCREASING FISHERMEN'S KNOWLEDGE IN PACKAGING FISH PRODUCTS - Siti Nuraini; Nirmala, Dwitha; Millati, Izzato (Universitas Airlangga, 2024)
Community public service is one of the knowledge transfer activities between academics and community. One of the community service activities carried out in Muncar District, Banyuwangi Regency provide solutions to fishermen's problems related to a lack of understanding of the packaging of fish caught by fishermen. For this reason, the solution to this problem is offer capacity building training with fish packaging. The results of the training showed that the fishing partner participants experienced increased knowledge in accordance with the targets and achievements of community service activities. It is hoped that after this activity there will be follow-up actions to strengthen institutions for fishing partners.